Transocular ultrasound measurement of the optic nerve sheath diameter can identify elevated intracranial pressure in trauma patients. (January 2016) - Nash, Joshua E; O'Rourke, Colin; Moorman, Matthew L
Background: Prompt identification of elevated intracranial pressure (eICP) is life-saving. Physical exam alone often fails to identify this problem and invasive monitoring is not always utilized appropriately. A non-invasive, rapid, reliable technique to detect eICP is needed and optic nerve sheath diameter (ONSD) is known to be a valid surrogate. Historically, ONSD in patients with eICP above 20 mmHg varied from 0.5 to 0.7 cm. Receiver operator curves predict that diameters below 0.5 to 0.58 cm correspond to normal pressures. Interobserver variability is low (0.01–0.03 cm). The learning curve was 25 and 10 procedures for novice and experienced sonographers, respectively. We report our initial experience using ultrasound to measure ONSD during initial trauma evaluation. Study design: Transocular ultrasound was used to determine ONSD after traumatic brain injury. Data were correlated with CT and exam findings or measured ICP. Measurements were performed by a single trauma surgeon. Time to perform the measurement was recorded. Relevant literature from the past 15 years was reviewed. Results: Physical exam was not a reliable indicator of eICP. In patients with eICP requiring surgery, ONSD averaged 0.62 cm. Normal pressures were ensured if the ONDS was <0.50 cm (95% CI 0.469–0.540 cm, p < 0.001). Intraobserver variability was low (0.01–0.02 cm). Average time to perform the exam was less than 2 min. Conclusions: Determining ONSD with ultrasound is easy to learn, precise, and inexpensive. An ONSD of less than 5 mm ensures no eICP. This procedure can be added to the evaluation of trauma patients with no delay in care. Future prospective studies may validate and incorporate this technique into the trauma surgeon's armamentarium.